Online Gaming: The Linkage on Social Identity and eCommerce - Wawan Hermawan; Rima Rahmayanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Internet network and online games penetration has gotten one of the driving variables for web based business development in Indonesia. Having an enormous populace, Indonesia gives a tremendous market to nearby and global online business. Alongside the advancement of web and web based gaming, the way of life and social behavior also the life styles of today's society in Indonesia has been shifted which demonstrated by the conveniences in using technological advances including in using online payment transaction methods, 48% of users who are between 26-35 years old are using various mobile payment methods for many purposes. This phenomenon describe that Indonesia become a potential target for e-commerce industry, including for gaming industry that utilizing e-commerce in generate revenues from selling games application and its accessories. If this potential can be utilized properly, it will certainly improve the national economy. Gaming business through web based business can offer incredible open doors for monetary development in. With increasing internet penetration, online gaming market is seen as an opportunity with a large potential for e-commerce. Developers across the world are expected to enter the booming online gaming market. This research aim to investigates the role of online gaming in increasing social identity effect to eCommerce, study in web based online community. Dota2 community in Bandung city, taken as samples from populace of Indonesian web based online gaming community.  The result reveals that online gaming contribute to the effect of social identity to eCommerce in Indonesia market as much as 79,1%.